Simplified Visual Cortex Model for Pattern Recognition - Cevikbas, Can; Yildirim, Tulay (IEEE, 2018)
A simplified primary cortex model is developed that can be used in pattern recognition. There are 1024 excitatory, 256 inhibitory cells. Integrate and Fire neuron model is chosen in the simulations. Each cell in the model may have three type of sources for input; sensory, connection and a constant background. Spike Timing Dependent Plasticity (STDP) is incorporated to change connection coefficient of two connected cells.
Keywords: Pattern recognition; visual cortex; neuron; Spike Timing Dependent Plasticity; CONNECTIONS; Computer Science; Engineering